2010
DOI: 10.1016/j.adolescence.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Proactive parenting practices during early adolescence: A cluster approach

Abstract: The purpose of the current study was to explore clusters of proactive parenting practices, and how they might vary as a function of parental demographics, the quality of the parent-child relationship, and the traits and behaviors of the adolescent child. Data were taken from the Flourishing Families Project, which includes 500 families with an early adolescent child (M age = 11.49). Findings suggested that there were four clusters of parents, and patterns were similar for mothers and fathers. Findings also sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 55 publications
(75 reference statements)
3
25
0
Order By: Relevance
“…However, many studies examining proactive control have found correlations with prosocial behavior (e.g., Krevans & Gibbs, 1996; Wang et al, 2007), which is not the same as the absence of problem behavior. Future research should acknowledge different forms of behavioral control, especially focusing on the understudied concept of proactive parenting (Padilla-Walker, Christensen, & Day, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies examining proactive control have found correlations with prosocial behavior (e.g., Krevans & Gibbs, 1996; Wang et al, 2007), which is not the same as the absence of problem behavior. Future research should acknowledge different forms of behavioral control, especially focusing on the understudied concept of proactive parenting (Padilla-Walker, Christensen, & Day, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Families were interviewed in their homes, with each interview consisting of a video task (not reported here) and questionnaires completed by the child, mother, and father. Our overall response rate of eligible families (families in the database with a child between the ages of 10 and 14) at Time 1 was 61% (for more information on the procedures and sample, see Padilla‐Walker, Christensen, & Day, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The effects were also relatively small in nature, which may be the result of the methodology used in the current study. Parents use a variety of approaches when monitoring the media, with meaningful differences (e.g., autonomy supportive vs. restrictive) potentially being captured in one broad category of media monitoring (Padilla-Walker, Christensen, & Day, 2011;Valkenburg et al, 2013). Media monitoring also occurs in the context of the overall parentechild relationship, which might vary considerably.…”
Section: Limitations Future Research and Conclusionmentioning
confidence: 99%